Portal Hypertension: Current Surgical Management - Wancata, Lauren M.; Connelly, Christopher R.; Orloff, Susan L. (Digestive Disease Interventions, 2022)
Portal hypertension occurs due to multiple disorders of the liver and its circulation. It is defined as an elevated pressure gradient between the portal circulation and the systemic circulation. The primary clinical consequences of portal hypertension are ascites and the development of portosystemic varices, which may cause life threatening hemorrhage. Modern management of portal hypertension includes medical, endoscopic therapy and transjugular intrahepatic portosystemic shunt placement by interventional radiology. Historically, portal hypertension was treated through the creation of surgical portosystemic shunts. In this chapter, the physiology of portal hypertension and the approaches to its management will be discussed. Specifically, the chapter will focus on indications, technical considerations, and types of surgical shunts used to treat portal hypertension, as well as literature supporting these procedures. Three case reports describing recent successful surgical shunt creation will be presented. Although portosystemic surgical shunt creation is performed far less frequently as medical, endoscopic and radiologic interventions have improved, this chapter illustrates that this procedure is a vital tool to be used in the treatment of portal hypertension.
Keywords: portal hypertension; transjugular intrahepatic portosystemic shunt; surgical portosystemic shunts; outcomes